Graphene spintronics: the European Flagship perspective. (7th July 2015) - Roche, Stephan; Åkerman, Johan; Beschoten, Bernd; Charlier, Jean-Christophe; Chshiev, Mairbek; Prasad Dash, Saroj; Dlubak, Bruno; Fabian, Jaroslav; Fert, Albert; Guimarães, Marcos; Guinea, Francisco; Grigorieva, Irina; et al.
Abstract: We review current challenges and perspectives in graphene spintronics, which is one of the most promising directions of innovation, given its room-temperature long-spin lifetimes and the ability of graphene to be easily interfaced with other classes of materials (ferromagnets, magnetic insulators, semiconductors, oxides, etc), allowing proximity effects to be harvested. The general context of spintronics is first discussed together with open issues and recent advances achieved by the Graphene Spintronics Work Package consortium within the Graphene Flagship project. Based on such progress, which establishes the state of the art, several novel opportunities for spin manipulation such as the generation of pure spin current (through spin Hall effect) and the control of magnetization through the spin torque phenomena appear on the horizon. Practical applications are within reach, but will require the demonstration of wafer-scale graphene device integration, and the realization of functional prototypes employed for determined applications such as magnetic sensors or nano-oscillators. This is a specially commissioned editorial from the Graphene Flagship Work Package on Spintronics. This editorial is part of the 2 D Materials focus collection on 'Progress on the science and applications of two-dimensional materials, ' published in association with the Graphene Flagship. It provides an overview of key recent advances of the spintronics work package as well as the mid-term objectives of the consortium.